Physico-chemical Characterization and Fertility Status of some Forest Nursery Soils of District Sirmour in Himachal Pradesh - Raina, J. N.; Kumar, Pardeep (Indian Forester, 2000)
The present study was undertaken to determine physico-chemical properties and fertility status of some forest nursery soils of District Sirmour in Himachal Pradesh_ Analysis of surface and sub-surface soil samples collected from the nurseries was carried out. The soil pH was found neutral and electrical conductivity was in safe limits (less than 0.8 dsm-1). The CEC values ranged between 7.1-16.8 cmol/kg soil and were higher in surface soils as compared to sub-surface soils. Organic carbon status was rated medium, while available N, P and K were categorized as low to medium, high and medium, respectively. Available Ca and Mg were in adequate amounts and SO4-S was found high. In order to have healthy nursery seedlings, there is a need to apply recommended doses of chemical fertilizers in conjunction with organic manures, however, phosphatic fertilizer application can be reduced by 25 percent of recommended dose.